Polypropylene-nylon composite material with self-adhesion to stainless steel

By using polypropylene-nylon composite material in stainless steel/polypropylene warm edge spacer, the problem of poor adhesion between stainless steel and polypropylene is solved, self-adhesion with stainless steel is achieved, extending service life and improving thermal insulation performance.

CN119264418AInactive Publication Date: 2025-01-07SHANDONG DONGCHEN ENG PLASTIC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411284775.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor adhesion between stainless steel and polypropylene causes the composite to easily break away during use and cracks are prone to occur at low temperatures, seriously affecting the service life of the stainless steel/polypropylene warm edge spacer.

Method used

Polypropylene-nylon composite material is used, and by adding polar nylon copolymer, it has good low temperature resistance, high toughness and good bonding properties. It is similar to polypropylene's melting point and good compatibility, and can self-adhesive with stainless steel. , no additional adhesive is required to achieve a firm bond.

Benefits of technology

The obtained polypropylene-nylon composite material has strong adhesion and stability, extending the service life of stainless steel + polypropylene-nylon hollow glass warm edge spacer, and has excellent thermal insulation performance and wide application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264418A_ABST
    Figure CN119264418A_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene-nylon composite material with self-adhesion to stainless steel. The polypropylene-nylon composite material is prepared from the following raw materials in parts by mass: 60-90 parts of polypropylene, 5-30 parts of a nylon copolymer and 0.1-5 parts of an antioxidant and / or a lubricant, wherein the preferable nylon copolymer is prepared from the following raw materials in parts by mass: 10-30 parts of caprolactam, 10-30 parts of nylon 66 salt, 30-50 parts of diacid and diamine, 5-25 parts of a deep eutectic solvent, 0.01-0.3 part of a catalyst and 0.01-0.3 part of an antioxidant, and the nylon copolymer is a polar material and is high in processability, low in hygroscopicity, good in compatibility with polypropylene and high in viscosity. The polypropylene-nylon composite material prepared by the invention shows an excellent bonding effect on stainless steel, has low hygroscopicity and good low-temperature bending property, effectively prolongs the service life of the stainless steel and polypropylene-nylon type hollow glass warm edge spacing bar, and has wide application and popularization values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, in particular to a polypropylene-nylon composite material with self-adhesiveness to stainless steel. Background Art

[0002] As a highly efficient building energy-saving material, hollow glass is widely used because of its good heat insulation, sound insulation, aesthetics and practicality, and the ability to reduce the deadweight of buildings. It is of great significance to the construction industry in reducing energy consumption and carbon emissions of buildings.

[0003] As an important accessory of insulating glass, spacers can effectively improve the performance of insulating glass. Traditional insulating glass uses metal aluminum spacers. Although the structure is strong, its high thermal conductivity leads to serious heat loss in the edge area, thereby reducing the overall thermal insulation performance and energy-saving effect. The warm edge spacers of insulating glass have excellent thermal insulation performance, outstanding sound insulation effect, excellent weather resistance, simple installation method and other characteristics and are widely concerned and applied. CN113072774 A discloses an insulating warm edge spacer and its preparation method and application, which is made of the following raw materials in parts by weight: 8-20 parts of butyl rubber, 15-30 parts of the first polymer, 8-15 parts of the second polymer, 10-15 parts of insulating filler, 12-25 parts of water absorbent, 10-15 parts of pigment filler, 10-20 parts of thickening filler, to form a spacer that meets the comprehensive requirements of strength, adhesion, insulation, viscoelasticity, etc., mainly to meet the use requirements of insulating glass. CN111978631A discloses a polypropylene warm edge spacer and a preparation method thereof, comprising the following raw material components by weight: 35-45 parts of extrusion-grade polypropylene, 5-10 parts of compatibilizer, 5-15 parts of mica, 35-50 parts of glass fiber, 0.3-0.8 parts of antioxidant, 0.2-0.4 parts of weathering agent, 0.1-0.3 parts of nucleating agent, 1-3 parts of silicone powder and 0.1-0.3 parts of fluorine-containing elastomer. The prepared polypropylene warm edge spacer effectively solves the problem of die precipitates in the production process, avoids scratches on the surface of the warm edge spacer and the mold, and has ultra-high rigidity and flatness. It can be seen that the development and utilization of warm edge spacers with different performances play an important role in improving the performance of insulating glass and promoting its application.

[0004] There are generally three types of common warm edge spacers: thermoplastic material, stainless steel / polypropylene, and glass fiber reinforced / non-metallic composite film. Among them, stainless steel / polypropylene composite materials have both certain rigidity and good thermal insulation effect, and have broad application prospects. However, due to the poor adhesion between stainless steel and polypropylene, a specific adhesive is often required to fix the two. However, the fluidity of the adhesive is poor, and it is easy to cause loose adhesion due to uneven distribution during coating or extrusion, causing the composite material to detach, and it is easy to crack at low temperatures, seriously affecting the service life. Based on this, the preparation of a polypropylene-based material that has self-adhesion to stainless steel has become an urgent problem to be solved in the promotion and application of stainless steel / polypropylene warm edge spacers. Summary of the invention

[0005] In view of the above problems, the present invention discloses a polypropylene-nylon composite material with self-adhesiveness to stainless steel. The composite material takes polypropylene as a base material and is added with a polar nylon copolymer. The nylon copolymer has the properties of good low temperature resistance, high toughness, high adhesion, etc., is close to the melting point of polypropylene, and has good compatibility. The obtained polypropylene-nylon composite material has strong adhesion to stainless steel and good bonding stability. It can achieve firm bonding with stainless steel without adding additional adhesives, is not easy to crack, has excellent thermal insulation performance, and effectively prolongs the service life of stainless steel + polypropylene-nylon type insulating glass warm edge spacers.

[0006] In order to achieve the above purpose, the technical solution adopted is:

[0007] A polypropylene-nylon composite material having self-adhesiveness to stainless steel is made of the following raw materials in parts by weight:

[0008] Polypropylene 60-90 parts;

[0009] 5-30 parts of nylon copolymer;

[0010] Antioxidant and / or lubricant 0.1 to 5 parts.

[0011] Preferably, the polypropylene-nylon composite material is made of the following raw materials in parts by weight:

[0012] Polypropylene 75-90 parts;

[0013] 10-20 parts of nylon copolymer;

[0014] Antioxidant and / or lubricant 0.1 to 1 part.

[0015] Furthermore, the polypropylene is selected from any one of homopolypropylene and copolymer polypropylene or a mixture of the two in any proportion.

[0016] Furthermore, the antioxidant is one or more of hindered phenols, hindered amines, phosphites and thiols; the lubricant is one or more of stearic acid and its salts, butyl stearate, oleamide, and ethylene bisstearamide.

[0017] Furthermore, the nylon copolymer has a melting point of 140 to 175° C. and is made from the following raw materials in parts by weight:

[0018]

[0019] Preferably, the nylon copolymer is made of the following raw materials in parts by mass:

[0020]

[0021] Furthermore, the molar ratio of the diacid to the diamine is 1:0.9-1.1; the diacid is one or more of adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid; and the diamine is any one or both of decanediamine and dodecanediamine.

[0022] Furthermore, the low eutectic solvent is one or more of decanoic acid-methyl trioctyl ammonium chloride, menthol-pyruvic acid, menthol-acetic acid, menthol-lauric acid, and thymol-benzyl triethyl ammonium chloride.

[0023] Furthermore, the low eutectic solvent is a eutectic mixture formed by mixing two or more hydrogen bond acceptors and hydrogen bond donors, wherein the hydrogen bond acceptors are choline chloride, quaternary ammonium salts, quaternary phosphate salts, pyruvic acid, acetic acid, and lauric acid; and the hydrogen bond donors are menthol, thymol, and fatty acids.

[0024] Furthermore, the preparation method of the low eutectic solvent is: stirring and mixing the hydrogen bond donor and the hydrogen bond acceptor in a molar ratio of 3 to 5:1, and then heating the mixture in a 70-90°C water bath for 20-40 minutes to form a uniform and stable liquid, and vacuum drying the low eutectic solvent liquid at 70-90°C for 3-6 hours before use to obtain the low eutectic solvent.

[0025] Furthermore, the catalyst is sodium hypophosphite.

[0026] Furthermore, the antioxidant is one or more of copper halide, di(2,2,6,6-tetramethyl-3-piperidinylamino)-isophthalamide, and isophoronediamine.

[0027] The present invention provides a method for preparing a nylon copolymer, and the specific steps are as follows:

[0028] Caprolactam, nylon 66 salt, diacid and diamine, low eutectic solvent, catalyst and antioxidant are added into the reaction kettle according to the above-mentioned mass fractions. After nitrogen is passed to replace the air, the temperature is raised to 210-230°C, and polymerization is carried out under nitrogen protection. The pressure is raised to 0.8-1.2 MPa and maintained for 0.5-1.5 h. Then the pressure is reduced to normal pressure for reaction for 2-4 h, and the material is cooled and discharged to obtain nylon copolymer.

[0029] The present invention provides a method for preparing a polypropylene-nylon composite material having self-adhesiveness to stainless steel, and the specific steps are as follows:

[0030] The polypropylene, nylon copolymer, antioxidant and / or lubricant are fully mixed in a high-speed mixer according to the above-mentioned mass fractions to obtain a premix, and the premix is ​​extruded and granulated by a twin-screw extruder. The extrusion granulation temperature is set at 180-230° C. and the screw speed is set at 400-600 rpm to obtain a polypropylene-nylon composite material with self-adhesiveness to stainless steel.

[0031] The invention provides a polypropylene-nylon composite material having self-adhesiveness to stainless steel.

[0032] Mechanism of action: The present invention provides a nylon copolymer with strong processability, low hygroscopicity, good compatibility with polypropylene, high viscosity and good low temperature resistance. First, by introducing diacids and diamines, and regulating the polymerization process, several monomers are randomly copolymerized, and the microstructure of the material after copolymerization is asymmetric, reducing the formation of hydrogen bonds, greatly reducing the proportion of crystalline regions, and the melting point of the obtained nylon copolymer is close to that of polypropylene, between 140 and 175°C, and it is easy to be processed and formed with polypropylene. Secondly, the preferred low eutectic solvent has a structure (OH, -COOH) that can provide active hydrogen in the molecule, and has excellent hydrophobicity. Its active hydrogen structure is easy to be stably combined with the amide group by forming hydrogen bonds. Its own excellent hydrophobicity can improve the hygroscopicity of nylon, which is helpful for practical application. Thirdly, the low eutectic solvent in the nylon copolymer can form a polar-polar interaction between its anion and the NH of nylon, and a non-polar-non-polar interaction between its cation and polypropylene, so that the polypropylene-nylon composite material can be uniformly compounded without the need to add an additional compatibilizer during the preparation process. Finally, nylon copolymer is a polar material and has good adhesion to metals. The addition of low eutectic solvent allows it to be evenly compounded with polypropylene, thereby improving the polarity of the polypropylene-nylon composite material and showing self-adhesion to stainless steel.

[0033] Beneficial effects:

[0034] (1) The present invention obtains a preferred nylon copolymer by optimizing the formula design. The nylon copolymer has a melting point similar to that of polypropylene and good compatibility. In addition, the nylon copolymer has the characteristics of strong processability, low hygroscopicity, high viscosity, good low temperature resistance, and strong processability and usability.

[0035] (2) The scheme of the present invention uses polypropylene as the base material and adds a polar nylon copolymer to obtain a polypropylene-nylon composite material with polarity and adhesion, so that the further prepared polypropylene-nylon composite material exhibits excellent adhesion to stainless steel and has low hygroscopicity, which is conducive to practical application. It also has good bendability at low temperatures, effectively extending the service life of the stainless steel + polypropylene-nylon type insulating glass warm edge spacer, and has wide application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The invention relates to a polypropylene-nylon composite material prepared. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be specifically described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0038] (1) Material source and preparation

[0039] The raw materials used in the examples and comparative examples all use the same commercially available products from the following sources:

[0040] Polypropylene T30S is homopolymer polypropylene: Sinopec Zhenhai Refining and Chemical Company; caprolactam: Zhejiang Juhua Co., Ltd.; nylon 66 salt: BASF; dodecanedioic acid: Shanghai Cathay Biotechnology Co., Ltd.; decanediamine: Shanghai Gaoming Chemical Co., Ltd.; capric acid: Hebei Runbang Chemical Co., Ltd.; methyl trioctyl ammonium chloride: Jinan Yunuo Chemical Co., Ltd.; catalyst: sodium hypophosphite, Jiangyin Yuanxin Chemical Co., Ltd.; antioxidant: copper salt antioxidant, Dongguan Tailong New Materials Technology Co., Ltd.; lubricant: stearic acid amide, Jiangxi Zhilian New Materials Co., Ltd.

[0041] Preparation of diacid and diamine: dodecanedioic acid and decanediamine were mixed at a molar ratio of 1:1 to obtain a mixed solution.

[0042] Preparation of a low eutectic solvent: The hydrogen bond donor decanoic acid and the hydrogen bond acceptor methyltrioctylammonium chloride were added into a round-bottom flask with a stirring rod in a molar ratio of 3:1, and then the mixture was heated in a water bath at 80°C for 30 minutes to form a uniform and stable low eutectic solvent liquid. Before use, the low eutectic solvent liquid was vacuum dried at 80°C for 4 hours to obtain the low eutectic solvent.

[0043] (2) Preparation of nylon copolymers

[0044] The preparation method of nylon copolymer is as follows: caprolactam, nylon 66 salt, diacid and diamine low eutectic solvent, catalyst and antioxidant are added into a reaction kettle, the air is replaced by nitrogen, the temperature is raised to 220°C, polymerization is carried out under nitrogen protection, the pressure is raised to 1MPa and maintained for 1h, the pressure is then reduced to normal pressure for reaction for 3h, the material is cooled and discharged, and the nylon copolymer product is obtained.

[0045] ① Nylon copolymer 1 was prepared as follows by weight:

[0046]

[0047] The melting point of the nylon copolymer 1 prepared according to the above preparation method is 172°C, which meets the design requirements.

[0048] ② The mass fractions of nylon copolymer 2 are as follows:

[0049]

[0050] The melting point of the nylon copolymer 2 prepared according to the above preparation method is 163°C, which meets the design requirements.

[0051] ③ The mass fractions of nylon copolymer 3 are as follows:

[0052]

[0053] The melting point of the nylon copolymer 3 prepared according to the above preparation method is 160°C, which meets the design requirements.

[0054] ④ The mass fractions of nylon copolymer 4 are as follows:

[0055]

[0056]

[0057] The melting point of the nylon copolymer 4 prepared according to the above preparation method is 147°C, which meets the design requirements.

[0058] Example

[0059] The formula of Examples 1-6 is shown in Table 1

[0060] Table 1 Formulation of Examples 1-6

[0061] formula Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polypropylene T30S 89.7 89.7 89.7 89.7 84.7 79.7 Nylon copolymer 1 10 Nylon Copolymer 2 10 Nylon Copolymer 3 10 15 20 Nylon Copolymer 4 10 Lubricants 0.3 0.3 0.3 0.3 0.3 0.3

[0062] The preparation method of the polypropylene-nylon composite material of Example 1-6 is as follows:

[0063] According to the mass fractions shown in Table 1, polypropylene, nylon copolymer and lubricant are fully mixed in a high-speed mixer to obtain a premix, which is then sent to a twin-screw extruder for mixing, melting, homogenization and extrusion granulation. The extrusion granulation temperature is 180-230° C. and the screw speed is 400-600 rpm to obtain a polypropylene-nylon composite material with self-adhesiveness to stainless steel.

[0064] Comparative Example

[0065] 99.7 parts of polypropylene and 0.3 parts of lubricant are fully mixed in a high-speed mixer to obtain a premix, which is then sent to a twin-screw extruder for mixing, melting, homogenization, and then extrusion granulation. The extrusion granulation temperature is 180-230° C. and the screw speed is 400-600 rpm to obtain a polypropylene composite material.

[0066] Material performance testing

[0067] Adhesion test: The polypropylene-nylon composite material was extruded to prepare a 9A specification stainless steel + polypropylene-nylon insulating glass warm edge spacer that meets the JC / T 2453-2018 "Insulating Glass Spacer" standard. The peel strength between the polypropylene-nylon composite material and the stainless steel was tested by a tensile tester at a tensile speed of 10 mm / min.

[0068] Bending test: refer to JC / T 2453-2018 "Insulating Glass Spacer" for the bending test.

[0069] The material performance test results of the embodiments and comparative examples are shown in Table 2 below:

[0070] Table 2 Material performance test results of the embodiments and comparative examples

[0071]

[0072]

[0073] As shown in Table 2, the polypropylene-nylon composite material provided by the present invention is specially designed for the warm edge strip of insulating glass, and exhibits excellent adhesion properties, and can be firmly and stably attached to the stainless steel surface. Even after multiple bending tests, no cracks are found, and the right-angle bending performance in a low temperature environment is particularly outstanding. After formula optimization, it can be seen that the performance of nylon copolymer 3 is the best. When the formula of Example 6 is 79.7 parts of polypropylene, 20 parts of nylon copolymer 3, and 0.3 parts of lubricant, the obtained polypropylene-nylon composite material has the best performance.

Claims

1. A nylon copolymer, characterized in that: The melting point is 140-175°C and is made from the following raw materials in parts by weight:

2. The nylon copolymer according to claim 1, characterized in that: The nylon copolymer is made from the following raw materials in parts by mass:

3. The nylon copolymer according to claim 1, characterized in that: The molar ratio of the diacid to the diamine is 1:0.9-1.1; the diacid is one or more of adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid; and the diamine is any one or two of decanediamine and dodecanediamine.

4. The nylon copolymer according to claim 1, characterized in that: The low eutectic solvent is one or more of decanoic acid-methyl trioctyl ammonium chloride, menthol-pyruvic acid, menthol-acetic acid, menthol-lauric acid, and thymol-benzyl triethyl ammonium chloride; the catalyst is sodium hypophosphite; and the antioxidant is one or more of copper halide, di(2,2,6,6-tetramethyl-3-piperidinylamino)-isophthalamide, and isophorone diamine.

5. The method for preparing a nylon copolymer according to claims 1-4, characterized in that: Add caprolactam, nylon 66 salt, diacid and diamine, low eutectic solvent, catalyst and antioxidant into a reaction kettle, replace the air with nitrogen and heat to 210-230°C, polymerize under nitrogen protection, increase the pressure to 0.8-1.2 MPa and maintain for 0.5-1.5 h, then reduce the pressure to normal pressure and react for 2-4 h, cool and discharge the material to obtain nylon copolymer.

6. A polypropylene-nylon composite material having self-adhesiveness to stainless steel, characterized in that: Made from the following raw materials in parts by weight: Polypropylene 60-90 parts; 5 to 30 parts of the nylon copolymer according to claim 1; Antioxidant and / or lubricant 0.1 to 5 parts.

7. The polypropylene-nylon composite material according to claim 6, characterized in that: The polypropylene-nylon composite material is made of the following raw materials in parts by weight: Polypropylene 75-90 parts; 10 to 20 parts of the nylon copolymer according to claim 1; Antioxidant and / or lubricant 0.1 to 1 part.

8. The polypropylene-nylon composite material according to claim 6, characterized in that: The polypropylene is selected from any one of homopolypropylene and copolymer polypropylene or a mixture of the two in any proportion.

9. The polypropylene-nylon composite material according to claim 6, characterized in that: The antioxidant is one or more of hindered phenols, hindered amines, phosphites and thiols; the lubricant is one or more of stearic acid and its salts, butyl stearate, oleamide and ethylene bisstearamide.

10. The method for preparing the polypropylene-nylon composite material according to claims 6-9, characterized in that: The polypropylene, nylon copolymer, antioxidant and / or lubricant are fully mixed in a high-speed mixer to obtain a premix, and the premix is ​​extruded and granulated by a twin-screw extruder. The extrusion granulation temperature is set at 180-230° C. and the screw speed is set at 400-600 rpm to obtain a polypropylene-nylon composite material with self-adhesiveness to stainless steel.

Citation Information

Patent Citations

  • Polypropylene warm edge spacing bar and preparation method thereof

    CN111978631A

  • Preparation method of polyamide hot melt adhesive

    CN109321198A

  • Warm side spacing barand preparation method thereof

    CN110551341A

  • Polypropylene / nylon 6 alloy material as well as preparation method and application thereof

    CN114806006A